2019
DOI: 10.1038/s41531-019-0101-9
|View full text |Cite
|
Sign up to set email alerts
|

PINK1 phosphorylates ubiquitin predominantly in astrocytes

Abstract: Loss-of-function mutations in PINK1 are causally linked to recessively inherited Parkinson’s disease (PD), with marked loss of dopaminergic neurons in the substantia nigra that are required for normal movement. PINK1 is a nuclear-encoded mitochondrial-targeted kinase that phosphorylates a conserved serine at amino acid 65 (pS65) in ubiquitin as well as Parkin, another gene with loss-of-function mutations linked to recessive parkinsonism. The steady-state levels of PINK1 protein are very low, even in cells that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 49 publications
(60 reference statements)
0
30
0
Order By: Relevance
“…While the high penetrance of PINK1 mutations establish its critical function for maintaining neurons the activity of PINK1 in primary neurons has been difficult to detect. However, Barodia et al determined the levels of PINK1 in neurons, astrocytes, microglia, and oligodendrocyte progenitor cells (OPCs) cultured from wild type and PINK1 knockout rat pups and showed that PINK1-dependent ubiquitin phosphorylation is predominately in astrocytes suggesting that the contribution of astrocyte dysfunction to PD pathogenesis warrants further investigation ( 45 ).…”
Section: Astrocytes and Their Role In Parkinson's Diseasementioning
confidence: 99%
“…While the high penetrance of PINK1 mutations establish its critical function for maintaining neurons the activity of PINK1 in primary neurons has been difficult to detect. However, Barodia et al determined the levels of PINK1 in neurons, astrocytes, microglia, and oligodendrocyte progenitor cells (OPCs) cultured from wild type and PINK1 knockout rat pups and showed that PINK1-dependent ubiquitin phosphorylation is predominately in astrocytes suggesting that the contribution of astrocyte dysfunction to PD pathogenesis warrants further investigation ( 45 ).…”
Section: Astrocytes and Their Role In Parkinson's Diseasementioning
confidence: 99%
“…Considering the roles for α-synuclein in synaptic function in normal and pathological states, investigators often use two-hit models to explore potential synergistic interactions between α-synuclein dysfunction and genes associated with increased risk for PD. However, in light of studies demonstrating roles for PD risk genes in non-neuronal populations (Moehle et al, 2012 ; Booth et al, 2017 ; Sliter et al, 2018 ; Barodia et al, 2019 ), it is important to consider whether genes of interest are expressed in the same cell types in vivo before exploring their potential interactions. With the recent emergence of single-cell RNA sequencing technologies, it is now possible to explore the neuroanatomical colocalization of genes using publicly accessible databases (Saunders et al, 2018 ; Zeisel et al, 2018 ; Monzón-Sandoval et al, 2020 ; Yuste et al, 2020 ).…”
Section: Potential Mechanisms Contributing To Synapse Loss In Pdmentioning
confidence: 99%
“…Other studies have shown that PINK1 deficiency impairs both the formation of GFAP + - astrocytes during development and the proliferation of astrocytes upon stimulation with epidermal growth factor (EGF) or fetal bovine serum [ 143 ]. Recently, Barodia et al [ 108 ] found that PINK1-dependent ubiquitin phosphorylation is predominantly in astrocytes as compared to neuronal and other non-neuronal cell types, supporting the contribution astrocyte dysfunction to PD pathogenesis.…”
Section: Gene-environment Interactions Converge In the Modulation Of mentioning
confidence: 98%
“…Accumulating evidence indicates the expression of mutated genes, including SNCA , PRKN , PINK1 , DJ-1 , and LRRK2 in astrocytes and/or microglial cells and their implication in glial biology [22,106–112]. Importantly, the pathways regulated by these genes intersect the key cellular functions affected in Parkinson's disease, namely, the inflammatory response, endoplassmic reticulum (ER) stress, mitochondrial, lysosomal, proteosomal, autophagic and Wnt signaling functions [ [106] , [107] , [108] , [109] , [110] , [111] , [112] , [113] , [114] , [115] , [116] , [117] , [118] , [119] , [120] , [121] , [122] ]. Supporting evidence also come from genome-wide (GWA) and genome wide methylation data analysis, further suggesting that immune, mitochondrial and Wnt signaling pathways are associated not only with PD risk but also with PD progression [ [123] , [124] , [125] , [126] , [127] ] Strikingly, VPS35 gene located at 16q13-q21 chromosomal position and the two pathways, the Wnt signaling pathway, and retromer-mediated DMT1 missorting are proposed for the basis of VPS35 related PD [ 117 , 118 ].…”
Section: Gene-environment Interactions Converge In the Modulation Of mentioning
confidence: 99%